KOMUNIKASI PARTISIPATIF DINAS LINGKUNGAN HIDUP DAN KEBERSEIHAN KOTA PEKANBARU DALAM MENGELOLA SAMPAH PADA TEMPAT PEMBUANGAN AKHIR (TPA) DI KELURAHAN MUARA FAJAR TIMUR - Sakroni "; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Invironmental problems that exist in the Muara Fajar landfill, of course, the role of the City Government does not escape the role of the Pekanbaru City Sanitation Office in collaboration with the Muara Fajar sub-district to manage the garbage that will damage the environment around the Muara landfill site. fajar timur, for that there is a need for participatory communication between the so that people want and participate in the management of waste in their region. The purpose of this study was to determine the participatory communication strategy used by the Environment and Hygiene Office of Pekanbaru City in managing waste at the Final Disposal Site (TPA) in Muara Fajar Timur Village, how community participation and inhibiting factors of participatory communication.Informants in this study were 5 people, including: Head of Department / Sub-Sector/Representative in the Department of Environment and Cleanliness of Pekanbaru City, East Muara Fajar Village Head, TPA Leader / Overseer, TPA Members / Workers and the surrounding Community. The analysis of the data used is the analysis of qualitative data from the analysis of various data collected in the field. Then the data is classified based on certain criteria.The results of the research show that the participatory communication strategy of the Pekanbaru City Environment and Hygiene Office in managing waste in Muara Fajar Timur Village is direct socialization to the community using baleho, banners and circulars to related parties. In addition, community participation in waste management in Muara Fajar Timur Village is quite good, for the inhibiting factors of communication, community participation in waste management in Muara Fajar Timur Village includes internal and external factors such as incompetent human resources, lack of supporting funds, lack of adequate facilities from the Government, time constraints, and lifestyle or habits of citizens.Keywords : Participatory Communication, Environmental and Hygiene Office of the City of Pekanbaru, Managing Waste.